Національно-прецедентне ім'я Лесі Українки в рецепції мовців - Петренко, А. (Культура слова, 2020)
Автор статті вивчає феномен прецедентної особистості
Лесі Українки як культурно значущого явища національно-мовної
картини світу українців у рецепції сучасних мовців. Особливу увагу
звернено на внутрішній лексикон таких авторитетних носіїв мови,
як Олесь Гончар, Оксана Забужко, у назвах заголовків праць про Лесю
Українку. Текстова інтерпретація поетеси відображає особливості
сприйняття конкретної історико-культурної особистості як
мотиватора національно маркованого прецедентного імені. Зміна
засад вивчення життя і творчості письменниці відбивається в
диференційних ознаках її прецедентного імені, актуалізованих у
заголовках. The author of the article studies the phenomenon of the precedent
personality of Lesia Ukrainka as a culturally significant phenomenon of
the national-linguistic picture of the world of Ukrainians in the reception
of modern speakers. The author turned to the study of the internal lexicon
of such authoritative native speakers as Oles Honchar, Oksana Zabuzhko
on the example of the titles of works about Lesia Ukrainka. The textual
interpretation of this culturally significant figure reflects the peculiarities
of the perception of a particular historical and cultural personality as a
motivator of a nationally marked precedent name. The change in the
principles of studying the life and work of the writer is reflected in the
differential features of her precedent name, already actualized in the
headlines.
The role of Ukrainian literature of the XIX – beg. XX century in the
formation of a nationally conscious stratum of Ukrainian society and today
remains decisive. Awareness of the national idea, its crystallization in the
apt poetic word contributed to the unification of nationally indifferent
citizens to build an ideologically united, conciliar state. Texts and ideas,
images, sayings, sometimes written more than a hundred years ago, remain
meaningful and relevant to the modern speaker.
Analyzing the titles of articles and sections, we consider them as a
kind of associative-verbal network, which illustrates the author’s thoughtreceptive
actions and associations caused by the verbal motivator (proper
name-stimulus) “Lesia Ukrainka”. Thanks to this approach, we can
consider them as individual and as those that allow the identification and
description of differential features that form the core of the precedent
name, which actualizes a certain bundle of knowledge and assessments
related to the precedent personality of Lesia Ukrainka in the linguistic
consciousness of Oles Honchar and Oksana Zabuzhko.